Environmental Attitude and Behaviour among Students: Incorporating the Green Concept in Learning Outcome Based - Bashirun, Siti Norashikin; Razali, Masliza; Abdul Rahman, Afrah Hayati (Advances in Social Sciences Research Journal, 2023)
The adoption of green behaviour is critical to reduce the environmental impacts. In response to demands for environmental sustainability, the Higher Education Institution (HEI) is promoting green campus development more aggressively. Guided by Social Cognitive Theory (SCT), this paper aims to identify student’s environmental attitude and behaviour towards green concepts. Data was collected through an online survey among 116 students. The findings revealed recycling behavior was at low level, whereas students’ energy conservation was at high level practices. These findings are based on the notion that embedding “green office” topics in course syllabus might increase knowledge and further influence behavioural change regarding green behavior among university students. The findings could contribute to the development of a long-term green nation by incorporating environmental sustainability into learning outcomes based on a curriculum framework as the university students are expected to be the most informed and aware about environmental issues.